2016
DOI: 10.4236/ojog.2016.64025
|View full text |Cite
|
Sign up to set email alerts
|

Distribution of High-Risk Human Papillomavirus Genotypes in Precancerous Cervical Lesions in Ouagadougou, Burkina Faso

Abstract: Aims: We aimed at identifying the high-risk HPV genotypes associated with high-grade dysplastic cervical lesions in Burkina Faso. The available vaccines to Burkina Faso only protect against two high risk HPV genotypes: HPV 16 and 18. Are the genotypes identified in the high-grade precancerous lesions in this survey covered by the available vaccines? Methods: The detection and genotyping of high-risk HPV have been conducted based on 118 formalin-fixed and paraffin-embedded archived tissues using the "HPV Genoty… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
2

Year Published

2019
2019
2025
2025

Publication Types

Select...
7
1

Relationship

5
3

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 19 publications
0
4
2
Order By: Relevance
“…This population is similar to the study population of Traore et al [8] in Bobo-Dioulasso (Burkina Faso) whose age varied between 20 and 56 years with an average of 35.3 ± 0.6 years. Married women represented 48.8% of cases, which is less than the findings of Ouedraogo et al [9] that reported 76% of married women always from the same country (Burkina Faso). We found a percentage of 52.2% of women which do not use condoms.…”
Section: Socio-demographic Sexual and Behavioural Characterisation Of...contrasting
confidence: 61%
“…This population is similar to the study population of Traore et al [8] in Bobo-Dioulasso (Burkina Faso) whose age varied between 20 and 56 years with an average of 35.3 ± 0.6 years. Married women represented 48.8% of cases, which is less than the findings of Ouedraogo et al [9] that reported 76% of married women always from the same country (Burkina Faso). We found a percentage of 52.2% of women which do not use condoms.…”
Section: Socio-demographic Sexual and Behavioural Characterisation Of...contrasting
confidence: 61%
“…These prevalences were also variable according to the locality. In high-grade lesions and cancer cases, the prevalence was 48.8% and 72.31%, respectively [14,15]. Cervical cancer is the most common cancer in women worldwide in 45 countries and kills more women than all other forms of cancer in 55 countries.…”
Section: Hpv and Cervical Cancermentioning
confidence: 99%
“…In Burkina Faso, cervical cancer is the second most common cancer in women, with 1132 cases and 839 deaths estimated for 2020 [6]. Several studies have already been carried out to determine the prevalence of HPV infection in the general population in different regions and towns of the country [7] [8] [9] [10], among sex workers [11] [12], among women diagnosed with precancerous lesions [13] [14] [15], in those with invasive cervical cancer [16] [17], in pregnant women [18], in adolescents [19] and in people living with Human Immunodeficiency Virus (HIV) [20] [21] [22]. However, no studies have been carried out in women with hepatitis B (HBV) and hepatitis C (HCV) infection.…”
Section: Introductionmentioning
confidence: 99%